Analisis Peran Media Sosial dalam Peperangan Rohani (Spiritual Warfare): Strategi Pelayanan Digital dalam Menghadapi Disinformasi yang Mengikis Spiritualitas Kristen - Pujiwati Pujiwati (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2025)
This study examines the role of social media as an arena for contemporary spiritual warfare and its impact on Christian spirituality, particularly in the context of increasing digital misinformation. Using a mixed-methods approach, this research combines quantitative surveys and qualitative interviews to identify patterns of religious misinformation dissemination and its impact on doctrinal understanding, worship practices, and the faith identity of the congregation. The findings indicate that exposure to misinformation negatively affects the depth of spiritual practices, increases theological confusion, and creates "alternative authorities" promoted by digital influencers. Additionally, the lack of spiritual media literacy and the church's unpreparedness to serve in the digital space exacerbate the vulnerability of the congregation. This study concludes that the digital space has become a significant battlefield for spiritual warfare, requiring theological, pastoral responses, and enhanced integrated media literacy. Therefore, it is recommended to develop theology-based media literacy, provide training for digital leaders, and create contextual, evidence-based church content strategies to strengthen the spiritual resilience of the congregation in facing misinformation in the digital world.